“Novos complexos quadráticos planos contendo tiossemicarbazonas derivadas de salicilaldeído: investigação da atividade antitumoral em modelos celulares 2D e 3D”. - Teixeira, Tamara (Universidade Federal de São Carlos, 2026)
Cancer remains one of the leading causes of mortality worldwide, highlighting the need for the development of more selective and effective therapeutic agents. In this context, metal complexes containing thiosemicarbazones have attracted considerable interest due to their structural versatility and their potential to modulate relevant biological properties. The present study aimed to synthesize, structurally characterize, and evaluate the antitumor activity of new Pd(II), Pt(II), and Ni(II) complexes containing salicylaldehyde-derived thiosemicarbazones associated with triphenylphosphine. Characterization of the compounds by molar conductivity, infrared and UV–Vis spectroscopy, mass spectrometry, nuclear magnetic resonance, and single-crystal X-ray diffraction confirmed the formation of neutral complexes with distorted square-planar geometry, in which the thiosemicarbazones act as tridentate (O,N,S) ligands. The complexes exhibited high stability in solution, consistent with multidentate coordination and the structural rigidity of the system. Cell viability assays revealed that cytotoxic activity was restricted to complexes containing the D2 ligand, bearing two nitro groups, in ovarian cancer cell lines, with particular emphasis on the Pd(II) complex, which showed the highest activity. Morphological and clonogenic assays demonstrated that the PdD2 complex exerts both cytotoxic and cytostatic effects, in addition to displaying greater selectivity toward tumor cells. Mechanistic studies, employing fluorescent probes and flow cytometry, indicated that the compound induces cell death predominantly through apoptosis, associated with alterations in the cell cycle, loss of membrane integrity, and depolarization of the mitochondrial membrane potential. Furthermore, experiments in three-dimensional models demonstrated that the PdD2 complex retains its activity in more physiologically relevant microenvironments, affecting the morphology, growth, and viability of tumor spheroids. Taken together, these results position the PdD2 complex as a promising candidate for the development of new thiosemicarbazone-based antitumor agents.
"New square-planar complexes containing salicylaldehyde derived thiosemicarbazones: investigation of antitumor activity in 2d and 3d models."
Keywords: Complexos de paládio(II); Tiossemicarbazonas; Atividade antitumoral; Apoptose; Modelos tridimensionais; Palladium complexes(II); Thiossemicarbazones; Antitumor activity; Apoptosis; Three-dimensional models; CIENCIAS EXATAS E DA TERRA::QUIMICA; 3. Saúde e Bem-Estar